2018
DOI: 10.1103/physrevd.97.123513
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational waves from vacuum first-order phase transitions: From the envelope to the lattice

Abstract: We conduct large scale numerical simulations of gravitational wave production at a first-order vacuum phase transition. We find a power law for the gravitational wave power spectrum at high wavenumber which falls off as k −1.5 rather than the k −1 produced by the envelope approximation. The peak of the power spectrum is shifted to slightly lower wave numbers from that of the envelope approximation. The envelope approximation reproduces our results for the peak power less well, agreeing only to within an order … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
217
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(229 citation statements)
references
References 45 publications
12
217
0
Order By: Relevance
“…For the observed value of the Higgs mass, x > 0.11 in the SM and the methods described above predict a smooth cross-over. However, in certain regions of parameter space, scenarios beyond the SM can be matched on to the 3D effective theory described by (46). One can thereby extract information about the phase structure in BSM theories from existing SM lattice studies.…”
Section: A Phase Transition Parameters From the Latticementioning
confidence: 99%
See 3 more Smart Citations
“…For the observed value of the Higgs mass, x > 0.11 in the SM and the methods described above predict a smooth cross-over. However, in certain regions of parameter space, scenarios beyond the SM can be matched on to the 3D effective theory described by (46). One can thereby extract information about the phase structure in BSM theories from existing SM lattice studies.…”
Section: A Phase Transition Parameters From the Latticementioning
confidence: 99%
“…In order for (46) to be an accurate description of the long distance physics, the new degrees of freedom introduced in the model should be heavy at the PT (so that they can be integrated out), new contributions to higher-dimensionalal operators induced by integrating out the new fields should be small enough to neglect, and couplings should be small enough so that the perturbative matching procedure of DR accurately described the underlying theory. This matching onto the theory described by (46) has been performed for the singlet, doublet and triplet models (discussed further below) and existing lattice results used to study the phase structure in certain regions of parameter space. In each case, these studies [88,89,[115][116][117] have found phenomenologically viable regions of the parameter space predicting a first-order PT.…”
Section: A Phase Transition Parameters From the Latticementioning
confidence: 99%
See 2 more Smart Citations
“…1 This is encouraging for the application of semiclassical methods in the related problem of electroweak phase baryogenesis with very strong electroweak phase transitions. These typically create sharp transition walls and are often encountered in the context of models producing large, observable gravitational wave signals [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%